Literary and Arithmetic Schools of Uktus Factory (1735–1742): A Historical Analysis - A. M. Safronova (Научный диалог, 2024)
This article examines the activities of the schools established at the Uktus Factory, initiated by the proactive policies of V.N. Tatischev during his tenure as the head of the factories (1734–1739), aimed at engaging children from all factory residents in formal education. The study establishes enrollment figures for the schools over three-year intervals, details collective recruitment efforts, and presents the total number of students taught literacy and basic mathematics, alongside an analysis of the social and age demographics of the pupils. It demonstrates that during the establishment of a network of factory schools in 1735–1736, the movement of skilled workers to other factories due to production needs rarely interrupted children’s education, often resulting in a turnover of students at Uktus. The article characterizes the teacher, exiled Nikita Afanasyev, highlighting his proactive approach to enhancing the organization of literacy instruction. It identifies key dates regarding the commencement of arithmetic education at the Uktus Literary School in Yekaterinburg, the founding of the arithmetic school at the Uktus Factory, and the appointment of top students from the Yekaterinburg school to teach Uktus children under the supervision of teachers Fyodor Sannikov and Afanasy Kichigin. The reasons for the closure of the schools at the Uktus Factory in autumn 1742 and the sharp decline in student enrollment from 1743 onwards are also analyzed.